Advances in Site-Selective Acylation of Pyranosides: From Oligopeptide Catalysis to Immobilized Catalysts in Flow - Seitz, Alexander; Justus Liebig University Giessen (My University, 2025)
In the search for potential new applications for our group’s catalysts, we explored the idea of combining two catalytic motifs, that we have extensively studied before, in a multicatalytic reaction. The initial step involves performing a site-selective acetylation of partially protected pyranosides using a π-methyl-histidine (PMH)-containing oligopeptide catalyst. The resulting mono-alcohols could then be utilized in a selective, thiourea-catalyzed glycosylation reaction to generate 2-deoxy disaccharides. This thesis focuses on the first reaction of the proposed sequence. In the first part, we present the site-selective acylation of various methyl 4,6-O-protected pyranosides. We screened several tetrapeptide catalysts containing PMH and an adamantane moiety as the backbone. We identified catalysts capable of overcoming the intrinsic reactivity, which we determined using N-methylimidazole (NMI), for most of the pyranosides studied. To optimize the reaction conditions, we employed design of experiments (DOE) studies. We also investigated the impact of the 4,6-O-protecting group and the acylation reagent. Furthermore, we demonstrated that the selectivity of the reaction increased with the length of the applied peptide catalyst, suggesting that hydrogen-bonding interactions play a crucial role in selectivity. Finally, we showed that the observed reactivity could be maintained in more complex systems, as we successfully combined a benzylidene protection and the site-selective acetylation in a one-pot reaction. In the second part, we investigated the same pyranosides using peptide catalysts immobilized onto Wang-resin. We developed this approach to enhance the sustainability of our reaction, but also after initial studies concerning multicatalysis with thiourea and oligopeptide catalysts showed interference between the two, indicating that they must be separated locally. During the study, we demonstrated that we could easily synthesize the immobilized catalysts via solid-phase peptide synthesis (SPPS) and that they were still able to overcome the intrinsic reactivity of the substrates. We found that the catalysts could be reused for several reaction cycles with consistent results. Additionally, we showed that we could apply the catalyst in a continuous flow reaction without a significant loss in reactivity and selectivity. We used the long-term activity of the catalyst to convert large quantities of substrate and observed that the catalyst’s selectivity remained intact even after a temporary change in substrate.
Keywords: ddc:540